Optic disk boundary extraction using wavelet transform - Tan, Wei. (2008)
The retinal image on the ocular fundus photograph can provide phathological changes caused by some eye diseases such as glaucoma, which may lead to loss of vision. It can also indicate early signs of some systemic diseases such as diabetes and hypertension.